Audit Hours and Unit Audit Price of Industry Specialist Auditors: Evidence from Korea1. (30th June 2015) - Bae, Gil S.; Choi, Seung UK; Rho, Joon HWA
Abstract: Higher audit fees associated with auditor industry specialization could represent higher unit price charged by industry specialist auditors (ISAs) or the provision of a greater quantity of audit services. This study exploits a field setting in Korea, where the disclosure of audit hours is required in company annual reports, and finds that ISAs charge significantly higher total audit fees but also expend significantly greater audit hours than non‐ISAs. When audit fees and hours are considered together, the unit audit price of ISAs is significantly lower than that of non‐ISAs. This indicates that higher total audit fees associated with ISAs are likely to be attributable to greater audit hours associated with ISAs. However, greater audit hours for ISAs may suggest higher audit quality or may simply indicate that the additional audit work performed by ISAs is conducted by relatively cheaper junior auditors. Our work provides an alternative explanation for the higher total audit fees documented in the previous studies.